Estrutura e desempenho de hospitais gerais que atendem o SUS no estado de São Paulo - 2008-2013 - Bertolini, Silvia Regina [UNIFESP] (2016)
Introduction - Hospitals are complex and relevant organizations in the construction of health care networks, and consume approximately two thirds of the sector's expenditures, being preferred foci of intervention directed to the rationality, optimization and utilization of resources involved, due to limited resources and health needs to be met. Objective: To analyze whether there is a relationship between the structural components and geographical spaces with the performance of the general hospitals that attend SUS in the State of São Paulo, from 2008 to 2013. Structural components were considered: hospital size, administrative sphere , The nature of the organization that manages the hospital, and the components of geographic spaces: Metropolitan Region (RM) and the Health Care Network (RAS). Method - Quantitative modeling research for production analysis. Performance indicators in relation to production: number of hospitalizations, number of emergency / emergency visits, number of outpatient consultations and number of deliveries, to productivity: hospital occupancy rate, occupancy rate of supplementary beds, mean Permanence, turnover rate and replacement interval; And quality cesarean rate and overall mortality rate. Data source of SUS information systems available and publicized. Repeated Measure ANOVA was used to compare the continuous variables (performance) among categories of categorical variables (hospital characteristics) over the years. Multiple comparisons were made through the Tukey test, and in the comparisons between the years in the same category the Bonferroni correction was used. Statistical analysis was performed using SPSS 19.0 software. The level of significance was 5%. Sample composed of 420 general hospitals of the SUS of the State of São Paulo, active in the period 2008-2013. Specialized hospitals of high complexity and the long term were excluded. Results: The average number of 105 beds/hospital remained stable in the period, even with a reduction in the average beds in small hospitals. There was an increase in the average number of AIH in the period. Hospital sizes showed significant differences between them and in general the large hospitals performed better in productivity indicators.. The hospitals of the private administrative sphere presented significant differences in relation to the state and municipal spheres, which obtained better results. The hospitals managed by third parties presented significant differences in relation to those of the private administration. The differences in public administration hospitals, at the state and municipal level are partial and many without significant differences, that is, they have similarities. The results of the hospitals belonging to the metropolitan regions present statistically better and different results from outside RM hospitals.. Analyzes of the indicators by RAS did not present significant differences in the period, which could be related to the implementation of RAS and / or Attention Networks. Cesarean delivery rates are high and were not conclusive for quality. Conclusion: Statistical analyzes show that all SUS general hospitals in the period from 2008 to 2013 presented upward results in relation to production and productivity indicators, and in relation to quality this behavior is not positive. When compared to the types of characteristics, the results suggest that there is a relationship between the components of structure and geographical spaces and the performance of general hospitals. Considerations: The results of the study point to the increasing participation of the public sector in SUS hospital care, whether direct or indirect, through social organizations managing public hospitals, and which also presented better results compared to private administration. In this scenario, the responsibilities of public managers assert themselves in seeking mechanisms for planning, monitoring and evaluation of the results, comparing the best use of hospital resources, in favor of efficient health outcomes, which, although the indicators of the study in the period have evolved for the better, There are still gaps in productivity and quality that need to be addressed.